2022
DOI: 10.1021/acscatal.2c03580
|View full text |Cite
|
Sign up to set email alerts
|

(NHC)Ni(0)-Catalyzed Branched-Selective Alkene Hydrosilylation with Secondary and Tertiary Silanes

Abstract: Hydrosilylation is a valuable approach for the construction of organosilanes, which are precursors to silicone materials that are widely incorporated in our everyday lives. The industry currently relies primarily on Karstedt’s catalyst, Pt2(dvtms)3 (dvtms = 1,3-divinyltetramethyldisiloxane), a precious metal catalyst that exhibits linear selectivity, with regioselectivity favoring the branched product remaining an outstanding challenge. The use of more Earth-abundant, base-metal catalysts has been a recent foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 129 publications
1
15
0
Order By: Relevance
“…A good linear fit is obtained, however, by plotting the initial rate against [ 1 ] 1/2 (Figure B), which suggests that the rate of transfer hydrogenation is half-order with respect to catalyst loading. Consistent with previously reported monomeric catalysts, we propose that the half-order dependence with respect to [ 1 ] arises from a pre-equilibrium chloride dissociation from the catalyst resting state (see the Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…A good linear fit is obtained, however, by plotting the initial rate against [ 1 ] 1/2 (Figure B), which suggests that the rate of transfer hydrogenation is half-order with respect to catalyst loading. Consistent with previously reported monomeric catalysts, we propose that the half-order dependence with respect to [ 1 ] arises from a pre-equilibrium chloride dissociation from the catalyst resting state (see the Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…Finally, hydrosilylation catalyzed by Ni/ICy occurs to give alkyl silanes 4 and 5 . A related Ni/NHC catalysis for the hydrosilylation of alkenes, including vinyl arenes, has been developed by Cook and co-workers . According to their mechanistic proposal, the hydrosilylation proceeds via the Chalk–Harrod mechanism: oxidative addition of the Si–H bond to Ni(0), insertion of the alkene, and reductive elimination to give alkyl silanes.…”
Section: Discussionmentioning
confidence: 99%
“…Scheme 48 Ni/NHC-catalysed hydrosilylation of alkenes with 21, 31 and chlorosilanes. 120 Scheme 49 Ni/NHC-catalysed hydroamination of activated alkenes with 21 amines. 125 Preliminary computational calculations to determine the nature of bonding of the (NHC) 2 NiBr 2 complex were performed, which showed that the 1,2,4-triazole based NHC is a strong s-donating ligand like the common imidazole based NHC ligands (Chart 1).…”
Section: Hydroamination Of Alkenesmentioning
confidence: 99%
“…In 2022, Cook et al reported a Ni 0 /NHC-catalysed branched-selective hydrosilylation reaction of styrenes with 2°, 3° and chlorosilanes 120 (Scheme 48). Industrially relevant silanes, particularly those substituted with chlorine or alkoxy groups, have not been extensively studied in the field of base-metal catalysis.…”
Section: Hydrofunctionalisation Of Alkenesmentioning
confidence: 99%
See 1 more Smart Citation